Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/gcb.15328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human disturbance activities and environmental change factors on terrestrial nitrogen fixation

Abstract: Biological nitrogen (N) fixation plays an important role in terrestrial N cycling and represents a key driver of terrestrial net primary productivity (NPP). Despite the importance of N fixation in terrestrial ecosystems, our knowledge regarding the controls on terrestrial N fixation remains poor. Here, we conducted a meta-analysis (based on 852 observations from 158 studies) of N fixation across three types of ecosystems with different status of disturbance (no management, restoration [previously disturbed], a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 83 publications
2
15
0
Order By: Relevance
“…), biome, and BNF type (nodulating, bryophyte, litter, etc.) (Zheng et al, 2020). Therefore how BNF will change is spatially variable and not controlled by a single factor.…”
Section: Discussionmentioning
confidence: 99%
“…), biome, and BNF type (nodulating, bryophyte, litter, etc.) (Zheng et al, 2020). Therefore how BNF will change is spatially variable and not controlled by a single factor.…”
Section: Discussionmentioning
confidence: 99%
“…As temperatures and CO 2 concentrations increase and precipitation patterns change, the demand for N and thus increased N fixation may increase and exacerbate Mo limitation (Hungate et al., 2004; Zheng et al., 2020) in regions isolated from increasing N deposition inputs. While Mo limitation has been found across a few ecosystems, these studies have been concentrated in certain regions (Dynarski & Houlton, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, precipitation had no significant effect on N 2 -fixation (Figure 4a). Similarly, Dynarski et al (2019) reported no significant effect of precipitation on N 2fixation in litter but other studies showed that reduced precipitation had negative effects on N 2 -fixation in moss (Gundale et al, 2009;Gundale, Wardle, & Nilsson, 2012;Whiteley & Gonzalez, 2016;Zheng et al, 2020). The impact of drought on moss N 2 -fixation likely depends on the intensity, the duration and the frequency of the events (Gundale, Wardle, & Nilsson, 2012).…”
Section: Climatic and Site-specific Predictors Of Cyanobacterial Biom...mentioning
confidence: 99%